Aplicaciones pedagógicas del equipo licuadora industrial en procesos de transformación agroindustrial. - Larco Narváez, Héctor Efraín (2022)
The purpose of this work was to carry out pedagogical applications from operating manual, maintenance of industrial blender at Food Bromatology Laboratory in Agroindustrial Career at the Technical University of Cotopaxi. During of the bibliographic review development, it was taken into account to know the pedagogical applications that can be carried out, operation and maintenance of industrial blender. Therefore, their knowledge is relevant within the framework of the practical activities carried out in the laboratory and serves as a guide to respond to possible equipment damage. The importance of each manual is details information of the most importance, its operation and maintenance that must be carried out on industrial blender, such as: routine, preventive and corrective maintenance, in addition to safety measures for the personnel that will operate. the equipment, leading to extend useful life and reduce time for carrying out pedagogical practices. To verify the correct operation of industrial blender, pedagogical practices were carried out on grinding of corn for granulometric analysis, the extraction of mucilage from malva (stems and flowers) which has different uses, clarification, for medicinal purposes, fruit coating, etc.